A Meta-Analysis of the Risk Factors of Persistent Pulmonary Hypertension in Newborns - Zhou, Ran; Zheng, You-Ning; Zhang, Xin-Ying; Cheng, Ya-Ying (Frontiers in Pediatrics, 2021)
Objective: To determine the risk factors of persistent pulmonary hypertension of the newborn using a meta-analysis method and provide a reference for its clinical prevention and treatment. Methods: A meta-analysis was performed by searching the PubMed, Embase, Cochrane Library, China Biology Medicine Disc, Wanfang, and Chinese VIP journal databases, as well as the China National Knowledge Infrastructure. Results: A total of 22 references were included in the meta-analysis; the cumulative medical records comprised 7,937 cases, and 2,613,072 control cases were included. A total of 12 related risk factors were included (7 were associated with pregnant women and 5 were associated with newborns). Conclusion: Among the 12 associated risk factors included, the three most important and their combined odds ratio values and 95% CI were as follows: (1) pregnant women smoking, 4.85 (1.98–11.9) during pregnancy; (2) gestational weeks <37, 4.34 (1.64–11.5); (3) perinatal asphyxia, 3.9 (2.87–5.31).